Detranslation: Spanglish from a neurolinguistic point of view - López-García, Ángel (Círculo de Lingüística Aplicada a la Comunicación, 2014)
Despite currently growing sociolinguistic research on Spanglish, it is a very peculiar linguistic variety, which cannot be understood without a careful analysis of its neurolinguistic background. This paper argues that a theoretical neurolinguistic view on Spanglish has to consider the cortex, where English-like words are located, the limbic system, where Spanish paradigms are stored, and the bundles of nerves that bind up both of them. Spanglish is an example of detranslation, a kind of negative translation.